LEGAL REGULATION OF THE CIVIL SERVICE IN THE USSR IN THE 20S OF THE XX CENTURY - Vasyliev, Stanislav (The Journal of V. N. Karazin Kharkiv National University. Series Law, 2022)
Introduction. The effectiveness of the state's performance of its functions, ensuring the rights of citizens largely depends on the high-quality performance of official duties by civil servants. That is why the study of legal regulation of the conditions of public service in different historical periods is characterized by relevance. The purpose of the study is to establish the peculiarities of the legal regulation of civil service in the USSR in the 20s of the XX century. The source base for the study of the problem is the regulatory legal acts of the Ukrainian SSR, which regulated the legal status of the civil servant in the period under study.Summary of the main results of the study. At the beginning of the 20s of the 20th century, the civil state service was militarized. The conditions of civil state service were determined according to the legislation and by-laws, which regulated conditions of service for military personnel. Since 1922, the Code of Labor Laws of the USSR and the Provisional Rules on Service in State Institutions and Enterprises of the USSR became the legal basis for service. Measures of social protection of civil servants were determined according to the norms of labor legislation. The payment conditions of civil servants were defined in separate resolutions of the government of the USSR.Peculiarities of the criminal responsibility of civil servants for committing official crimes in the early 1920s were determined by the norms of separate resolutions of the government of the USSR. Separate chapters on responsibility for official crimes were provided for in the criminal codes of the Ukrainian SSR of 1922 and 1927. Civil servants were subject to disciplinary responsibility by the decision of a disciplinary court established by a trade union or district executive committee. Subsequently, the right to apply disciplinary sanctions was obtained by the direct superiors of the civil servant.Conclusions. During the studied historical period, no separate legislative act was adopted in the Ukrainian SSR that would comprehensively regulate the specifics of public service and social protection of civil servants. The legal status of a civil servant was determined on the basis of labor law norms.